EFFECT OF DIFFERENT pH ON HYDROLYSATE RENDEMENT EEL (Monopterus albus) PROTEIN USING Papain Enzyme - Priady Simatupang; Edison Edison; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT            Eel (Monopterusalbus) is one of the raw materials for protein hydrolyzate. Eel (M. albus) is known to have a complete amino acid composition. Protein hydrolyzate is made using enzymes. One of the factors that affect the characteristics of the protein hydrolyzate produced is pH. This study aims to determine the effect of pH on the hydrolysis of eel protein (Monepterusalbus) with the use of papain enzymes on yield. The method used is an experimental method with a non-factorial Completely Randomized Design (CRD) consisting of 3 treatment levels, namely P1 (pH 6.5), P2 (pH 7), P3 (pH 7.5). The analysis parameter is yield. The results showed that the yield of eel hydrolyzate treatment P1 (pH 6.5), P2 (pH 7), and P3 (pH 7.5) were 19.09%, 21.28%, and 22.26%, respectively. The highest yield of hydrolyzate was produced at pH 7. Keyword: papain enzyme, fish protein hydrolyzate, pH.